UNUSUALLY AGGRESSIVE MYOFIBROMATOSIS IN A NEONATE - Jitendra Hazarey; Shilpa Hazare; Girish Moghe (EL-Med-Pub, 2012)
Infantile myofibromatosis is a rare tumor of infancy. It is mesenchymal in origin and involves superficial structures or may be visceral. The lesions have been found in nearly all kinds of tissues, including the orbit, bone, lip, oral cavity, central nervous system, gastrointestinal tract, lungs, myocardium, liver, and biliary tree.